Singapore Government Securitization Measures against Transboundary Haze Pollution as a Non-Traditional Security Threat - Ramli, Muhammad (Parahyangan Center for International Studies, 2024)
Transboundary haze pollution (PALB) has developed into a critical concern for Southeast Asian countries in terms of transboundary issues and national security. This study aims to provide an understanding of the non-traditional threats that have become significant in front of countries, to demonstrate that the PALB issue is worthy of being included in the Non-Traditional Security (KNT) study, to provide an in-depth analysis of how the securitization transformation process has affected PALB issues in Singapore, to correlate the involvement of various actors in the ongoing securitization process, and to evaluate. This research uses a qualitative methodology to connect one variable to another in a direct and constructive manner, drawing on a broad theoretical foundation, most notably constructivism. It can be inferred that the government possesses complete authority to secure the smog issue. The community's response is critical in determining the success of haze securitization. Additionally, mass media and social media play a critical role in channeling popular opinion. Keywords: existential threat; securitization policy; constructivism approach; transboundary haze pollution; speech act